NIR-based Sensing System for Non-invasive Detection of Hemoglobin for Point-of-care Applications - Kumar, Yogesh; Dogra, Ayush; Shaw, Vikash; Kaushik, Ajeet; Kumar, Sanjeev (Current Medical Imaging, 2022)
Background: Hemoglobin is an essential biomolecule for the transportation of oxygen, therefore, its assessment is also important to be done frequently in numerous clinical practices. Traditional invasive techniques have concomitant shortcomings, such as time delay, the onset of infections, and discomfort, which necessitate a non-invasive hemoglobin estimation solution to get rid of these constraints in health informatics. Currently, various techniques are underway in the allied domain, and scanty products are also feasible in the market. However, due to the low satisfaction rate, invasive solutions are still assumed as the gold standard. Recently introduced technologies effectively evolved as optical spectroscopy and digital photographic concepts on different sensing spots, e.g., fingertip, palpebral conjunctiva, bulbar conjunctiva, and fingernail. Productive sensors develop more than eight wavelengths to compute hemoglobin concentration and four wavelengths to display only Hb-index (trending of hemoglobin) either in disposable adhesive or reusable cliptype sensor’s configuration. Objective: This study aims at an optimistic optical spectroscopic technique to measure hemoglobin concentration and conditional usability of non-invasive blood parameters’ diagnostics at point-ofcare. Methods: Two distinguishable light emitting sources (810 nm and 1300 nm) are utilized at isosbestic points with a single photodetector (800-1700 nm). With this purpose, reusable finger probe assembly is facilitated in transmittance mode based on the newly offered sliding mechanism to block ambient light. Results: Investigation with proposed design presents correlation coefficients between reference hemoglobin and every individual feature, a multivariate linear regression model for highly correlated independent features. Moreover, principal component analytical model with multivariate linear regression offers mean bias of 0.036 and -0.316 g/dL, precision of 0.878 and 0.838 and limits of agreement from -1.685 to 1.758 g/dL and -1.790 to 1.474 g/dL for 18 and 21 principal components, respectively. Conclusion: The encouraging readouts emphasize favorable precision; therefore, it is proposed that the sensing system is amenable to assess hemoglobin in settings with limited resources and strengthening future routes for the point of care applications.
Keywords: sliding mechanism